The Diachrony of Tone Sandhi Evidence from Southern Min Chinese - Lin, Qing.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book investigates the diachronic change of the tone sandhi of Southern Min Chinese, which is known for its synchronic arbitrariness and opacity. It argues that in final-prominent tone sandhi, the change of final tones and the change of non-final tones can be highly independent and essentially different from each other. Accordingly, it proposes a new position-based diachronic approach to study the separate evolution of tones occurring at different positions. This book is the first study to rigorously and systematically explore the diachrony of Southern Min tone sandhi.
Chapter 1. Introduction -- Chapter 2. A Position-based Diachronic Perspective to Tone Sandhi -- Chapter 3. Experiment Methodologies -- Chapter 4. Tonal Changes in Chao-Shan -- Chapter 5. Tonal Changes in Zhang-Quan -- Chapter 6. Conclusions -- Bibliography -- Appendix A Monosyllabic Reading List -- Appendix B Disyllabic Reading List.
Keywords: Historical linguistics; Linguistics; Asia -- Languages; Historical Linguistics; Theoretical Linguistics / Grammar; Asian Languages